The molecular functions of RIT1 and its contribution to human disease. Issue 15 (7th August 2020) - Van, Richard; Cuevas-Navarro, Antonio; Castel, Pau; McCormick, Frank
Abstract : RIT1 is a member of the Ras family of GTPases that direct broad cellular physiological responses through tightly controlled signaling networks. The canonical Ras GTPases are well-defined regulators of the RAF/MEK/ERK pathway and mutations in these are pathogenic in cancer and a class of developmental disorders termed RASopathies. Emerging clinical evidences have now demonstrated a role for RIT1 in RASopathies, namely Noonan syndrome, and various cancers including lung adenocarcinoma and myeloid malignancies. While RIT1 has been mostly described in the context of neuronal differentiation and survival, the mechanisms underlying aberrant RIT1-mediated signaling remain elusive. Here, we will review efforts undertaken to characterize the biochemical and functional properties of the RIT1 GTPase at the molecular, cellular, and organismal level, as well as provide a phenotypic overview of different human conditions caused by RIT1 mutations. Deeper understanding of RIT1 biological function and insight to its pathogenic mechanisms are imperative to developing effective therapeutic interventions for patients with RIT1-mutant Noonan syndrome and cancer.